2012
DOI: 10.1111/j.1540-8159.2012.03509.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Observations and Outcome of Ventricular Tachycardia Ablation in Patients with Left Ventricular Assist Devices

Abstract: Ablation of VT in LVAD patients is feasible and can result in a markedly decreased VT burden with a reduction of ICD shocks. The subsequent discontinuation of intravenous antiarrhythmic medications may facilitate hospital discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 12 publications
3
21
0
1
Order By: Relevance
“…Similarly, there was no interference of the HeartMate II pump on the magnetic field with the ability to accurately track the MediGuide catheter tip (Figure 3), nor with the quality of electrograms observed on the ablation catheter. This finding is consistent with previous reports that have suggested no significant electromagnetic interference between the HeartMate II device and radiofrequency delivery; electroanatomic mapping with the CARTO system, which generates a magnetic field of 2.5–65 µT at frequencies of 2, 2.2, and 3 kHz (Biosense Webster; Johnson & Johnson, New Brunswick, NJ), or EnSite NAVx system (frequency 5.7 kHz; St. Jude Medical) 7, 8, 9, 10…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, there was no interference of the HeartMate II pump on the magnetic field with the ability to accurately track the MediGuide catheter tip (Figure 3), nor with the quality of electrograms observed on the ablation catheter. This finding is consistent with previous reports that have suggested no significant electromagnetic interference between the HeartMate II device and radiofrequency delivery; electroanatomic mapping with the CARTO system, which generates a magnetic field of 2.5–65 µT at frequencies of 2, 2.2, and 3 kHz (Biosense Webster; Johnson & Johnson, New Brunswick, NJ), or EnSite NAVx system (frequency 5.7 kHz; St. Jude Medical) 7, 8, 9, 10…”
Section: Discussionsupporting
confidence: 91%
“…Although some studies speculated that VT in LVAD patients could be linked to the cannula, 3,14 others have reported findings similar to ours. 10,11 Cantillon et al 10 found that 75% of VTs originated from the intrinsic scar versus 14% from the cannula area. They also found some VTs caused by microreentrant mechanisms (7%) and bundle branch reentry (3.5%).…”
Section: Discussionmentioning
confidence: 99%
“…8 Catheter ablation offers an opportunity to reduce or eliminate these events and has been shown to be feasible in single center studies. [9][10][11] However, the electrophysiological characteristics and outcomes associated with catheter ablation for VAs in patients with Heart Mate II (HM2) device (Thoratec) have not yet been evaluated in a multicenter series.…”
mentioning
confidence: 99%
“…Until now publications usually dealt with VTs originating near the cannula, but there are scarce data about VTs arising from the intrinsic scar [1][2][3][4][5].…”
Section: Sirsmentioning
confidence: 99%